2014
DOI: 10.1007/s00276-014-1386-3
|View full text |Cite
|
Sign up to set email alerts
|

The frontal branch of the facial nerve: can we define a safety zone?

Abstract: There exists no real area of anatomical safety in the temporal region. It seems, however, possible to define areas of relative safety that would be of great help for the surgeon or the morphologist wishing to approach pathologies of this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…We focused on six different branches, as described in previous studies (Hwang et al, ; Sachs et al, ; Kurita et al, ; Davies et al, ; Chatellier et al, ; Righini et al, ; de Bonnecaze et al, ; Frigerio et al, ; Choi et al, ): the temporal, frontal, zygomatic, buccal, marginal mandibular, and cervical branches. In our dissections, the frontal branch was defined as the branch arising from the temporal branch and destined to the mimetic muscles of the fronto‐orbital region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on six different branches, as described in previous studies (Hwang et al, ; Sachs et al, ; Kurita et al, ; Davies et al, ; Chatellier et al, ; Righini et al, ; de Bonnecaze et al, ; Frigerio et al, ; Choi et al, ): the temporal, frontal, zygomatic, buccal, marginal mandibular, and cervical branches. In our dissections, the frontal branch was defined as the branch arising from the temporal branch and destined to the mimetic muscles of the fronto‐orbital region.…”
Section: Methodsmentioning
confidence: 99%
“…Facial‐nerve palsy is the most common complication during facial surgery. Most authors interested in the anatomy of the extracranial facial nerve have studied the division of branches or have defined cross‐sectional areas to avoid facial‐nerve lesions (Hwang et al, ; Davies et al, ; de Bonnecaze et al, ). Multiple innervations of the mimetic muscles are familiar to facial surgeons but are relatively poorly described.…”
Section: Introductionmentioning
confidence: 99%
“…However, Yang and Yoo reported that the FN branches formed a loop or plexiform on the condylar area in 52 % of patients, and thus, superficial landmarks cannot be provided for the FN branches within the condylar area [71]. In the case of the Tbr, which crosses the condyle and zygomatic arch, de Bonnecaze et al found that there is no actual safe area in the temporal region [6]. The Bbr generally proceeds forwards below the orbit as it distributes to the midface musculature of the upper lip, cheek, and nose area.…”
Section: Facial Nerve Trunk and Its Major Branches At The Condylar Areamentioning
confidence: 97%
“…The FN constitutes a complicated plexus, and they anastomose with twigs from other cranial nerves, and as a result, it is very difficult to provide a nerve-free safe zone within the condylar area for the prevention of FN branch injury (Fig. 5) [1,6,12,13,24,26,35,68,70,71]. Laurentjoye et al recommended that three cutaneous reference lines from the tragus could serve as safe nerve-free area for dissection; the tragus-lateral canthus line for Tbr, the tragus-ala nasi line for Zbr and the tragus-lip corner line for Bbr [36].…”
Section: Facial Nerve Trunk and Its Major Branches At The Condylar Areamentioning
confidence: 99%
“…This branch of facial nerve is mostly located under this oblique line [3]. Temporal branch is the most susceptible branch of facial nerve that would be damaged during the approaches to the TMJ [4]. This nerve branch lies under the surface of temporoparietal fascia [5].…”
Section: Regional Nervesmentioning
confidence: 99%